EFFECT OF NITROGEN, ROOT STIMULATOR, AND GIBBERELLIC ACID ON A SPECIFIC CHARACTERISTICS OF PEACH SAPLINGS - & Joody, Altotanje (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed to evaluate the effect of nitrogen fertilizer, organic root stimulator and gibberellic acid on some growth characters of peach saplings cv. Red June for two consecutive seasons 2017-2018 at College of Agricultural Engineering Science, University of Baghdad. Different nitrogen (Urea 46%N) rates (0,50,75 gm) with three concentrations of organic stimulator (0,0.5,1 gm.L-1) and two rates of Ga3 (0,50 mg.L-1) were applied in a factorial scheme (3×3×2). Results revealed that the individual and interactive effect of applying nitrogen, root stimulator and GA3 significantly increased the studied characters, the interaction at N2D1G1 has improved the leaf dry weight (42.00%), shoot dry weight (61.33 %), Relative water content (RWC) (60.00%), N (2.68%), P (0.414%) and K (1.94 %) for season 2017, while the treatment N2D2G1 had the highest values at leaf dry weight (46.00 %), shoot dry weight (64.00%), RWC (74.00%) and leaf content of N (2.39%), P (0.56%), and K (1.99%) for season 2018.